Utilization of wood waste into briquettes as an alternative fuel substitute for kerosene in Skouw Yambe Village, Jayapura City - Hendry Y. Nanlohy; Helen Riupassa; Jusuf Haurissa; Susi Marianingsih; Syamsudin Usman (Universitas Muhammadiyah Magelang, 2022)
The existence of wood waste along the coast of Skouw Yambe is an abundant natural potential that has not been utilized properly. This Community Service activity aims to utilize the waste into briquettes as an alternative fuel to replace kerosene. The method used in this activity is the socialization, practice and training of making briquettes starting from collecting and drying raw materials, making wood charcoal, refining wood charcoal, mixing wood charcoal with adhesives, printing briquettes, drying briquettes, and cooking trials using briquettes. The result from this community service program is that the people of Skouw Yambe village can have excellent skills and abilities in producing household-scale briquettes from wood waste.